Budget Planning Revenue Sources and the Use of Village Expenditure - Luh Putu Parendra Indra Devi; I Ketut Suamba; Gede Mekse Korri Arisena; Rahayu Relawati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Tabanan Regency still faces obstacles to effectively managing village finances, as shown by the budget surplus (SiLPA). Bali Province has achieved the lowest SiLPA ratio. Therefore, it is necessary to re-optimize financial management, taking into account the diverse challenges faced by the 133 villages. Furthermore, given that Bali is a major source of agricultural production and employment, effective village financial management will significantly impact agriculture's development. This study examined the budget planning process in Tabanan Regency, the sources of revenue for villages in Tabanan Regency, the use of village budgets in Tabanan Regency, and the role of village financial management on agricultural development. This study employed qualitative and quantitative descriptive analysis to examine budget planning, revenue sources, and the utilization of village budgets in 20 villages. Qualitative descriptive analysis was employed to investigate the impact of village finance management on agricultural development. The results show that the village finances in Tabanan Regency have been managed according to the principles of transparency, accountability, participation, and budget discipline. The primary source of revenue in Tabanan Regency is Transfer Revenue. The majority of village expenditures in Tabanan Regency are allocated towards village administration. Village finance management is crucial for promoting agricultural development and enhancing the village economy.